Spinco Model 135A Spectromonitor
This liquid chromatography recording detector system consists of a dual-beam spectrophotometer, a pH meter, and a conductivity cell.
Keywords: Liquid chromatography; Spectrum analysis; Hydrogen-ion concentration--Measurement--Instruments; Spectrophotometer; Beckman Instruments, Inc.; Beckman Instruments, Inc. Spinco Division